Luisa Robles de Dávalos: History, gender and heritage management in the district of San Jerónimo - Cusco (1979-1980) - Contreras Marticorena, Luis (2019)
Between the years of 1960 and 1980 a series of political events shook the country, military coups interchanged with dictatorships and democratic elections. Simultaneously institutions were appearing which were given the task of protecting the cultural heritage. Lima and Cusco — for their historical wealth and built heritage — began to benefit from cultural policies proposed by institutions such as UNESCO and the National Institute of Culture of Peru (INC, today the Ministry of Culture). In this context, the presence of women in politics or positions of importance was overshadowed by the social environment. However, during the time mentioned, a number of women at the national level occupied political positions and contributed to the urban changes at that moment. Unfortunately, in historical research this influence goes quite unnoticed, this is the case of Luisa Robles de Dávalos, former mayor of the District of San Jerónimo in Cusco, who completed two terms, the first between 1967-70 and the second between 1979-80. This article is an excerpt from the study on the Gender Approach in the local politics of Cusco, related to the History of Cultural Heritage Management in Peru.